Biofloc technology and cockroach (Nauphoeta cinerea) insect meal-based diet for Nile tilapia: Zootechnical performance, proximate composition and bacterial profile - Tubin J.S.B.* (2023)
© 2023 Jiovani Sergio Bee Tubin et al., published by Sciendo.Different inclusion levels of cockroach meal Nauphoeta cinerea (CM) were investigated in diets for tilapia (Oreochromis niloticus) reared in biofloc systems in substitution of the soybean meal. Five treatments were evaluated (0, 5, 10, 15 and 20% of CM inclusion) using three experimental units per treatment. The experiment lasted for five weeks with units stocked with 10 juveniles (3.00±0.25 g) per replicate. Water quality, zootechnical performance, bacteriological profile, and proximate composition were analyzed and monitored. Zootechnical data was submitted to a regression analysis up to second order. No differences were verified regarding feed conversion, survival and productivity. The CM presented high protein levels (66.84%), high estimated gross energy (5270 kcal kg-1), low lipids (6.07%) and mainly long-chain saturated fatty acids. Different bacteriological profiles were identified including species which may be potentially pathogenic and responsible for degrading organic matter. The overall results indicated that it is possible to include CM up to 10% in diets for tilapia juveniles raised in biofloc systems.